Associations between emotion regulation and remission following cognitive behavioural therapy for adults with bulimia nervosa. (9th April 2022) - Trainor, Claire; Michael, Megan L.; Lampe, Elizabeth W.; Presseller, Emily K.; Juarascio, Adrienne; Manasse, Stephanie M.
Abstract: Objective: Emotion regulation (ER) deficits are associated with illness severity in individuals with bulimia nervosa. We examined whether baseline ER abilities are associated with remission following enhanced cognitive behavioural therapy for eating disorders (CBT‐E). Method: Participants ( N = 50, 85.0% female) receiving CBT‐E completed a measure (yielding a global score and six subscale scores) of ER pre‐treatment. Remission was assessed by the Eating Disorder Examination at post‐treatment and follow‐up. Analyses tested associations between baseline ER and behavioural, cognitive, or full remission at post‐treatment and three‐month follow‐up. Results: Lower global ER abilities, measured by the Difficulties in Emotion Regulation Scale, were associated with lower likelihood of behavioural and full, but not cognitive, remission at post‐treatment. Specifically, individuals low in emotional clarity and impulse control were less likely to be behaviourally remitted. Those low in emotional acceptance, awareness, clarity, or strategies to manage emotion were less likely to be fully remitted. Global ER scores were not associated with any remission type at follow‐up. Discussion: Baseline ER deficits were associated with lower likelihood of behavioural or full remission at post‐treatment. However, ER was less associated with remission at follow‐up, indicating that ER is most important during treatment. Findings highlight a need for targeted treatments aimed at improving ER. Highlights: Baseline Emotion regulation (ER) predicted behavioural, but not cognitive, remission following cognitive behavioural therapy for eating disorders (CBT‐E), such that those with baseline deficits were less likely to be remitted. Further, baseline ER predicted full remission, in the same direction. Baseline ER was not associated with any type of remission three months post‐treatment. Specific domains of ER may differentially impact remission categories.